2014
DOI: 10.1038/nprot.2014.135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nuclear RNA interference in human cells by subcellular fractionation and Argonaute loading

Abstract: RNA interference (RNAi) is well known for its ability to regulate gene expression in the cytoplasm of mammalian cells. In mammalian cell nuclei, however, the impact of RNAi has remained more controversial. A key technical hurdle has been a lack of optimized protocols for the isolation and analysis of cell nuclei. Here we describe a simplified protocol for nuclei isolation from cultured cells that incorporates a method for obtaining nucleoplasmic and chromatin fractions and removing cytoplasmic contamination. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(172 citation statements)
references
References 34 publications
2
168
1
1
Order By: Relevance
“…AGO2 is found in the endoplasmic reticulum (ER), which is contiguous with the nuclear envelope (Stalder et al 2013). We have previously developed protocols for separating nuclei from ER (Gagnon et al 2014b). Western blot analysis demonstrated that nuclear preparations lacked ER protein or cytoplasmic contaminants (Fig.…”
Section: Purification Of Nuclear or Cytoplasmic Ago2mentioning
confidence: 99%
See 2 more Smart Citations
“…AGO2 is found in the endoplasmic reticulum (ER), which is contiguous with the nuclear envelope (Stalder et al 2013). We have previously developed protocols for separating nuclei from ER (Gagnon et al 2014b). Western blot analysis demonstrated that nuclear preparations lacked ER protein or cytoplasmic contaminants (Fig.…”
Section: Purification Of Nuclear or Cytoplasmic Ago2mentioning
confidence: 99%
“…Purification of cytoplasmic and nuclear extract from T47D or Flag-AGO2 cells was performed as described previously (Gagnon et al 2014b) with a few modifications. Rather than using sonication to lyse nuclei, a 27-gauge needle was used.…”
Section: Extract Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study highlighted the importance of ensuring that isolated nuclei are free from endoplasmic reticulum (ER) to avoid contamination with cytoplasmic AGO-containing complexes. Recently, a comprehensive protocol was developed to ensure that purified nuclei are free from ER contamination [134] .…”
Section: Tgsmentioning
confidence: 99%
“…To recapitulate this effect in vitro, siRNAs were designed against the two lncRNAs using the Dharmacon siDesign tool (http://dharmacon.gelifesciences.com/design-center/). SiRNAs have previously been used to reduce the expression of nuclear lncRNAs and it is now known that the factors required for RNAi are indeed present in the nuclear compartment [254,[355][356][357]. SiRNA C1-2 and siRNA C1-3 were chosen for further experiments to silence CUPID1, with siRNA C1-3 being less efficient but still producing a consistent 50-70% reduction in CUPID1 levels (Figure 4.18A).…”
Section: Chaptermentioning
confidence: 99%